2004
DOI: 10.1002/hbm.20033
|View full text |Cite
|
Sign up to set email alerts
|

Executive processes in Parkinson's disease: FDG‐PET and network analysis

Abstract: It is assumed widely that the clinical expression of Parkinson's Disease (PD), both motor and cognitive, is subtended by topographically distributed brain networks. However, little is known about the functional neuroanatomy of executive dysfunction in PD. Our objective was to validate further in a PD group the use of network analysis to assess the relationship between executive processes and pathological disorganization of frontostriatal networks. We studied 15 patients with idiopathic PD, and 7 age-matched no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 44 publications
(61 reference statements)
3
76
0
3
Order By: Relevance
“…However, it is important to note that although treatment-mediated changes in PDRP expression correlate significantly with improvement in UPDRS ratings, the metabolic and clinical disease descriptors are not interchangeable. Indeed, intersubject differences in these measures generally have less than 50% of their variability in common, as observed in correlations between PDRP scores and motor UPDRS ratings obtained at baseline or during therapy (e.g., Feigin et al, 2002;Lozza et al, 2004;Trošt et al, 2006). Thus, it is likely that the objective imaging-based network measure may provide unique information about disease severity or the Test-retest reliability of Parkinson's disease-related brain network Y Ma et al treatment response that is not captured by the simpler and more accessible clinical rating scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that although treatment-mediated changes in PDRP expression correlate significantly with improvement in UPDRS ratings, the metabolic and clinical disease descriptors are not interchangeable. Indeed, intersubject differences in these measures generally have less than 50% of their variability in common, as observed in correlations between PDRP scores and motor UPDRS ratings obtained at baseline or during therapy (e.g., Feigin et al, 2002;Lozza et al, 2004;Trošt et al, 2006). Thus, it is likely that the objective imaging-based network measure may provide unique information about disease severity or the Test-retest reliability of Parkinson's disease-related brain network Y Ma et al treatment response that is not captured by the simpler and more accessible clinical rating scales.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that this disease is associated with a specific spatial covariance pattern involving metabolic abnormalities in basal ganglia thalamocortical functional/anatomic pathways (Eidelberg et al, 1994(Eidelberg et al, , 1997. Indeed, this PD-related covariance pattern (PDRP) has been detected in multiple independent patient populations scanned in the resting condition (Moeller et al, 1999;Feigin et al, 2002;Lozza et al, 2004;Asanuma et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Some neuroimaging studies have proposed that changes in striatal dopamine levels can modulate certain cognitive processes and that level of cognitive impairment may be dependent on the level of dopamine depletion (Cropley et al, 2006). Consistent with this hypothesis, positron emission tomography (PET) studies performed both in healthy subjects (Mehta et al, 2005), following tyrosine and phenylalanine-induced depletion, and patients with Parkinson's disease (PD) (Marie et al, 1999;Lozza et al, 2004) have shown significant correlation between executive task performances and striatal dopamine denervation.…”
Section: Introductionmentioning
confidence: 93%
“…This characteristic pattern (FIG. 1A) 1) has been validated in multiple populations of unmedicated PD patients 4,36,43 ; 2) can be detected early in the disease course 34 ; and 3) correlates consistently with disease severity and duration. 3,44 We also found that PDRP activity correlates with nigrostriatal dopamine deficiency as determined by [ 18 F]-fluorodopa PET 34,45 and with internal pallidal (GPi) single unit activity recorded during surgery.…”
Section: Metabolic Brain Network In Parkinson S Diseasementioning
confidence: 99%